Surface adhesion of fusion proteins containing the hydrophobins HFBI and HFBII from Trichoderma reesei - Linder, Markus (Cold Spring Harbor Laboratory Press, 2002)
Hydrophobins are surface-active proteins produced by filamentous fungi, where they seem to be ubiquitous. They have a variety of roles in fungal physiology related to surface phenomena, such as adhesion, formation of surface layers, and lowering of surface tension. Hydrophobins can be divided into two classes based on the hydropathy profile of their primary sequence. We have studied the adhesion behavior of two Trichoderma reesei class II hydrophobins, HFBI and HFBII, as isolated proteins and as fusion proteins. Both hydrophobins were produced as C-terminal fusions to the core of the hydrolytic enzyme endoglucanase I from the same organism. It was shown that as a fusion partner, HFBI causes the fusion protein to efficiently immobilize to hydrophobic surfaces, such as silanized glass and Teflon. The properties of the surface-bound protein were analyzed by the enzymatic activity of the endoglucanase domain, by surface plasmon resonance (Biacore), and by a quartz crystal microbalance. We found that the HFBI fusion forms a tightly bound, rigid surface layer on a hydrophobic support. The HFBI domain also causes the fusion protein to polymerize in solution, possibly to a decamer. Although isolated HFBII binds efficiently to surfaces, it does not cause immobilization as a fusion partner, nor does it cause polymerization of the fusion protein in solution. The findings give new information on how hydrophobins function and how they can be used to immobilize fusion proteins.